2020
DOI: 10.1002/pa.2130
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear energy consumption and economic growth in the UK: Evidence from wavelet coherence approach

Abstract: The aim of this present study is to assess the causal link between nuclear energy consumption and economic growth in the United Kingdom using Toda Yamamoto causality and wavelet coherence tests with the objective of responding to the following questions: (a) Does consumption of nuclear energy lead to economic growth in the United Kingdom and/or does economic growth lead to the consumption of nuclear energy sources in the United Kingdom, and (b) if so, why? The findings from wavelet coherence reveal that change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 55 publications
1
43
0
Order By: Relevance
“…In understanding these impacts, the environmental Kuznets curve (EKC) is widely adapted to investigate the interactive influences and casual relationship of components that promotes emission (Shahbaz et al 2013;Tariq et al 2017). Hence, EKC model explains the complementary relatedness of socio-eco-environmental variables as they influence carbon emissions, as empirical investigations on the theme has attracted contrary views due to differences in The role of tourism on emissions is an addition to a number of other interrelated macroeconomic variables (Adedoyin et al 2020a, b;Adedoyin et al 2020a, c, b;Adedoyin and Zakari 2020;Etokakpan et al 2020;Kirikkaleli et al 2020;Udi et al 2020). For instance, tourism is recognized as a driver of economic expansion (Ouyang and Lin 2017;Wang et al 2016;Hossain 2011;Yu et al 2012) which in turn is responsible for the increasing CO 2 emission globally (Dogan and Seker 2016;Dogan and Turkekul 2016;;Wang et al 2016;Dogan et al 2020;Ertugrul et al 2016;Inglesi-Lotz and Dogan 2018;Moutinho et al 2018;Wang et al 2017;Zameer and Wang 2018;Wen and Shao 2019;Yasmeen et al 2020) and this threatens the environmental sustenance since this emission leads to extensive global warming.…”
Section: Introductionmentioning
confidence: 99%
“…In understanding these impacts, the environmental Kuznets curve (EKC) is widely adapted to investigate the interactive influences and casual relationship of components that promotes emission (Shahbaz et al 2013;Tariq et al 2017). Hence, EKC model explains the complementary relatedness of socio-eco-environmental variables as they influence carbon emissions, as empirical investigations on the theme has attracted contrary views due to differences in The role of tourism on emissions is an addition to a number of other interrelated macroeconomic variables (Adedoyin et al 2020a, b;Adedoyin et al 2020a, c, b;Adedoyin and Zakari 2020;Etokakpan et al 2020;Kirikkaleli et al 2020;Udi et al 2020). For instance, tourism is recognized as a driver of economic expansion (Ouyang and Lin 2017;Wang et al 2016;Hossain 2011;Yu et al 2012) which in turn is responsible for the increasing CO 2 emission globally (Dogan and Seker 2016;Dogan and Turkekul 2016;;Wang et al 2016;Dogan et al 2020;Ertugrul et al 2016;Inglesi-Lotz and Dogan 2018;Moutinho et al 2018;Wang et al 2017;Zameer and Wang 2018;Wen and Shao 2019;Yasmeen et al 2020) and this threatens the environmental sustenance since this emission leads to extensive global warming.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a similar fashion where macroeconomic variables are linked with economic growth across many country case studies (Balsalobre‐Lorente et al, 2020; Etokakpan, Adedoyin, Vedat, & Bekun, 2020; Kirikkaleli, Adedoyin, & Bekun, 2020; Udi, Bekun, & Adedoyin, 2020), we found that previous studies examined the link between migration and trade separately (see, e.g., Bougheas & Nelson, 2012; Ma & Tang, 2019; Sgrignoli, Metulini, Schiavo, & Riccaboni, 2015) and other studies have also been conducted to investigate the link between governance (mostly via quality of institutions) and trade (see Gani & Scrimgeour, 2016; Sugimura and Murakami, 2016; Wu, Li, & Samsel, 2012). Our thorough investigations show that no attempt has been made previously to look at the two relationships together in one study for Europe.…”
Section: Introductionmentioning
confidence: 91%
“…The study of energy consumption has been found to influence economic growth (Udi et al 2020). or may not in other instances, depending on the form of energy consumed (Kirikkaleli 2020). Energy generally comes in various forms such as fossil fuel and electricity.…”
Section: Energy Consumption and Economic Growthmentioning
confidence: 99%